The extracellular matrix component perlecan/HSPG2 regulates radioresistance in prostate cancer cells - Samaržija, Ivana; Lukiyanchuk, Vasyl; Lončarić, Marija; Rac-Justament, Anja; Stojanović, Nikolina; Gorodetska, Ielizaveta; Kahya, Uğur; Humphries, Jonathan D.; Fatima, Mahak; Humphries, Martin J.; Fröbe, Ana; Dubrovska, Anna; et al. (Frontiers in Cell and Developmental Biology, 2024)
Radiotherapy of prostate cancer (PC) can lead to the acquisition of radioresistance through molecular mechanisms that involve, in part, cell adhesion-mediated signaling. To define these mechanisms, we employed a DU145 PC model to conduct a comparative mass spectrometry-based proteomic analysis of the purified integrin nexus, i.e., the cell-matrix junction where integrins bridge assembled extracellular matrix (matrisome components) to adhesion signaling complexes (adhesome components). When parental and radioresistant cells were compared, the expression of integrins was not changed, but cell radioresistance was associated with extensive matrix remodeling and changes in the complement of adhesion signaling proteins. Out of 72 proteins differentially expressed in the parental and radioresistant cells, four proteins were selected for functional validation based on their correlation with biochemical recurrence-free survival. Perlecan/heparan sulfate proteoglycan 2 (HSPG2) and lysyl-like oxidase-like 2 (LOXL2) were upregulated, while sushi repeat-containing protein X-linked (SRPX) and laminin subunit beta 3 (LAMB3) were downregulated in radioresistant DU145 cells. Knockdown of perlecan/HSPG2 sensitized radioresistant DU145 RR cells to irradiation while the sensitivity of DU145 parental cells did not change, indicating a potential role for perlecan/HSPG2 and its associated proteins in suppressing tumor radioresistance. Validation in androgen-sensitive parental and radioresistant LNCaP cells further supported perlecan/HSPG2 as a regulator of cell radiosensitivity. These findings extend our understanding of the interplay between extracellular matrix remodeling and PC radioresistance and signpost perlecan/HSPG2 as a potential therapeutic target and biomarker for PC.